Peningkatan Kepuasan Kerja Melalui Penguatan Efikasi Diri Dan Supervisi Kepala Sekolah - Agustin, Nurleila; Rubini, Bibin; Sumardi, Sumardi (JURNAL MANAJEMEN PENDIDIKAN, 2024)
INCREASING JOB SATISFACTION THROUGH STRENGTHENING SELF-EFFICACY AND SUPERVISION OF SCHOOL PRINCIPALSThis study aims to find strategies and ways to increase teacher job satisfaction by examining the strength of the relationship between teacher job satisfaction and self-efficacy and principal supervision. This study uses a survey method with a correlational approach and SITOREM analysis to determine priorities and recommend indicators that need to be improved. The research sample was 119 non-permanent teachers in State Elementary Schools in East Bogor District. The results of the quantitative study found that all variables had a significant positive relationship, which, individually or collectively, showed a very strong relationship with job satisfaction. Based on the analysis stage of Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM), it can be identified the strength of influence between the research variables, and based on the weight of each indicator derived from the independent variable that has the largest contribution, the priority order of the indicators is obtained. Indicators that need to be improved immediately.